Viral Load Suppression after Enhanced Adherence Counseling and Its Predictors among High Viral Load HIV Seropositive People in North Wollo Zone Public Hospitals, Northeast Ethiopia, 2019: Retrospective Cohort Study - Gedefaw Diress; Samuel Dagne; Birhan Alemnew; Seteamlak Adane; Amanuel Addisu (AIDS Research and Treatment, 2020)
Background. The World Health Organization currently encourages enhanced adherence counseling for human immunodeficiency virus (HIV) seropositive people with a high viral load count before a treatment switch to the second-line regimen, yet little is known about viral load suppression after the outcome of enhanced adherence counseling. Therefore, this study aimed to assess viral suppression after enhanced adherence counseling sessions and its predictors among high viral load HIV seropositive people. Methods. Institutional-based retrospective cohort study was conducted among 235 randomly selected HIV seropositive people who were on ART and had a high viral load (>1000 copies/ml) from June 2016 to January 2019. The proportion of viral load suppression after enhanced adherence counseling was determined. Time to completion of counseling sessions and time to second viral load tests were estimated by the Kaplan–Meier curve. Log binomial regression was used to identify predictors of viral re-suppression after enhanced adherence counseling sessions. Result. The overall viral load suppression after enhanced adherence counseling was 66.4% (60.0–72.4). The median time to start adherence counseling session after high viral load detected date was 8 weeks (IQR 4–8 weeks), and the median time to complete the counseling session was 13 weeks (IQR 8–25 weeks). The probability of viral load suppression was higher among females (ARR = 1.2, 95% CI: 1.02–1.19) and higher educational status (ARR = 1.7, 95% CI: 1.25–2.16). The probability of viral load suppression was lower among people who had 36–59 months duration on ART (ARR = 0.35, 95% CI: 0.130–0.9491) and people who had > 10,000 baseline viral load count (ARR = 0.44, 95% CI: 0.28–0.71). Conclusion. This study showed that viral suppression after enhanced adherence counseling was near to the WHO target (70%) but highlights gaps in time to enrolment into counseling session, timely completion of counseling session, and repeat viral load testing after completing the session.